Improving Quality of Biology Learning with Contextual Teaching Learning (CTL) Approach Accompanied by Development of Subject Specific Pedagogy (SSP) at The Students in Grade X-E of SMA Negeri 1 Kartasura Academic Year 2011/2012 - Suraya, Ana; Sajidan, Sajidan; Karyanto, Puguh (BIO-PEDAGOGI, 2013)
The aim of this research is improve quality of biology learning for teacher performance, conditioning class, student attitude in class, and student motivation of learning in student grade of X-E SMA Negeri 1 Kartasura academic year 2011/2012. This research refers to The Classroom Action Research with subject were 39 students in grade of X-E SMA Negeri I Kartasura. The sources of data consist of information from teacher and student, places and events that happened during teaching and learning process, and also some documents. The data of research is collected through observation sheet, questionnaire and interview. The research uses triangulation as validation data. The research uses descriptive as analytic data. The result of this research shows that there has been improvement percentage of the quality of biology learning in every aspect which includes teacher performance, conditioning of class, student attitude, and student motivation of learning. The percentage’s mean of the questioner result in  sequence I is  conditioning of class 72,56%; student attitude 65,14%; student motivation of learning 75,02%, and of observasi data are teacher performance 83,33%; conditioning of class 71,54%; student attitude 63,37%; student motivation 75%.  The reflection of the first sequence shows that students having low of argument explanation in the learning goal, so the researcher gave further treatment in sequence II.  In the second sequence the percentage’s mean of the questioner result is teacher performance 93,33%; conditioning of class 82,69%; student attitude 86,08%; student motivation 86,22%, in this cycle every quality of biology  learning aspects improved in line with the target. It can be concluded from the research that Contextual Teaching Learning (CTL) approach application accompained by Subject Specific Pedagogy (SSP) can improve quality of biology learning of students in grade X-E SMA Negeri 1 Kartasura academic year 2011/2012. Key Words: Quality of biology learning, Contextual Teaching Learning, Subject Specific Pedagogy